The Lie of Global Prosperity : How Neoliberals Distort Data to Mask Poverty and Exploitation - Donnelly, Seth (Book collections on Project MUSE., 2019)
"This book deconstructs the assumption that global poverty has fallen dramatically, and lays bare the spurious methods of poverty measurement and data on which the dominant prosperity narrative depends. Here is carefully researched documentation that global poverty-and the inequalities and misery that flourish within it-remains massive, afflicting the majority of the world's population. Donnelly goes further to analyze just how global poverty, rather than being reduced, is actually reproduced by the imperatives of capital accumulation on a global scale. Just as the global, environmental catastrophe cannot be resolved within capitalism, rooted as it is in contemporary mechanisms of exploitation and plunder, neither can human poverty be effectively eliminated by neoliberal 'advances.'"--